Modifications in Dietary Fat Quality Are Associated with Changes in Serum Lipids of Older Adults Independently of Lipid Medication - Buyken, Anette; Flood, Victoria; Rochtchina, Elena; Nestel, Paul; Brand-Miller, Jennie; Mitchell, Paul (The Journal of Nutrition)

Immigrational Background Affects the Effectiveness of a School-based Overweight Prevention Program Promoting Water Consumption - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Toschke, André M.; Reinehr, Thomas; Kersting, Mathilde (Obesity)

Relative validity of a self-completion 24 h recall questionnaire to assess beverage consumption among schoolchildren aged 7 to 9 years - Muckelbauer, Rebecca; Libuda, Lars; Kersting, Mathilde (Public Health Nutrition)
Abstract Objective Drinking habits in children are associated with diet quality, but validated assessment tools for large-scale studies in young children are lacking. Therefore, we validated a self-completion 24 h recall questionnaire (RQ) focusing on beverage consumption with a 24 h weighed record (WR). Design Thirty-five voluntary participants from the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study cohort aged 7–9 years completed the RQ. The illustrated RQ required ticking the number of glasses of seven beverage categories consumed in five time intervals in the previous 24 h. As a reference, parents completed weighed records of their child’s diet. Agreement between the RQ and WR was tested by classification into consumers and non-consumers (kappa coefficients, κ ), by the children’s ability to estimate the exact beverage and total volume consumed (Wilcoxon signed-rank test, Spearman rank correlation), and by ranking children according to reported beverage volumes. Results The RQ and WR showed a good level of agreement for classifying participants into consumers and non-consumers of the single beverage categories ( κ values between 0·78 and 0·94). Correlation coefficients for the volume of the single categories ranged between 0·81 and 0·91. The total beverage volume was overestimated in the RQ, on average, by 114 ml ( P = 0·015). Agreement in ranking into tertiles by beverage volume was moderate to good for juice/soft drinks ( κ = 0·44), milk ( κ = 0·57) and water ( κ = 0·70), but fair for the total beverage volume ( κ = 0·23). Conclusions Our self-completion 24 h RQ could estimate the consumption of several beverage categories among young children at the group level, but quantification of total beverage volume was flawed.

Relation of Dietary Glycemic Index, Glycemic Load, and Fiber and Whole-Grain Intakes During Puberty to the Concurrent Development of Percent Body Fat and Body Mass Index - Cheng, G.; Karaolis-Danckert, N.; Libuda, Lars; Bolzenius, K.; Remer, T.; Buyken, Anette E. (American Journal of Epidemiology)

Long-term process evaluation of a school-based programme for overweight prevention - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Child: Care, Health and Development)

A Simple Dietary Intervention in the School Setting Decreased Incidence of Overweight in Children - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Reinehr, Thomas; Kersting, Mathilde (Obesity Facts)

Promotion and Provision of Drinking Water in Schools for Overweight Prevention: Randomized, Controlled Cluster Trial - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Toschke, A. M.; Reinehr, T.; Kersting, M. (PEDIATRICS)

Erfolgreich Computer und Internet in Grundschulen integrieren – eine empirische Analyse aus Sicht der Schulentwicklungsforschung - Eickelmann, Birgit; Schulz-Zander, Renate; Gerick, Julia (Europäisierung der Bildung - Konsequenzen und Herausforderungen für die Grundschulpädagogik)

The Dagstuhl Core - Dumitrescu, Theodor; Kepper, Johannes; Kornstädt, Andreas; Röwenstrunk, Daniel; Roland, Perry; Sapp, Craig; Selfridge-Field, Eleanor; Wiering, Frans; Wiggins, Geraint A.

Soft drinks and body weight development in childhood: is there a relationship? - Libuda, Lars; Kersting, Mathilde (Current Opinion in Clinical Nutrition and Metabolic Care)

Getränkeverzehr und Übergewicht bei Kindern - Libuda, Lars; Muckelbauer, R.; Kersting, M. (Journal für Ernährungsmedizin)

Einfluss des Konsums von Erfrischungsgetränken auf den Ernährungs- und Gesundheits¬status von Kindern - Libuda, Lars (Ernährungsumschau)

DONALD News: Zusammenhang zwischen dem Verzehr von Erfrischungsgetränken und dem Knochenstatus von Kindern und Jugendlichen. - Libuda, Lars; Remer, Thomas; Kersting, M. (Ernährungsumschau)

Associations of fat and cholesterol intake with serum lipid levels and cardiovascular disease: The EURODIAB IDDM Complications Study* - Toeller, M.; Buyken, Anette; Heitkamp, G.; Scherbaum, W.A.; Krans, H.M.J; Fuller, J.H. (Experimental and Clinical Endocrinology & Diabetes)

A new FFQ designed to measure the intake of fatty acids and antioxidants in children - Stiegler, Petra; Sausenthaler, Stefanie; Buyken, Anette; Rzehak, Peter; Czech, Daniel; Linseisen, Jakob; Kroke, Anja; Gedrich, Kurt; Robertson, Claire; Heinrich, Joachim (Public Health Nutrition)
Abstract Objective The present paper describes the systematic development of an FFQ to assess the intake of fatty acids and antioxidants in school-aged children. In addition, a validation study applying 24 h dietary recalls was performed. Design Using the variance-based Max_r method, a list of eighty-two foods was compiled from data obtained by 3 d weighed dietary records. The foods were used to design an FFQ, the comprehensibility of which was evaluated in a feasibility study. In addition, the FFQ was validated in a subset of 101 children from the German Infant Nutritional Intervention Study (GINI PLUS) against one 24 h dietary recall. Results The feasibility study attested a good acceptance of the FFQ. Mean intake of foods compared well between the FFQ and the 24 h dietary recall, although intake data generated from the FFQ tended to be higher. This difference became less apparent at the nutrient level, although the estimated average consumption of arachidonic acid and EPA using the FFQ still exceeded values recorded with the 24 h recall method by 45 % and 29 %, respectively. Conclusions On the basis of the systematic selection process of the food list, the established practicability of the FFQ and the overall plausibility of the results, the use of this FFQ is justified in future epidemiological studies.

Glucocorticoids and body fat associated with renal uric acid and oxalate, but not calcium excretion, in healthy children - Shi, Lijie; Berkemeyer, Shoma; Buyken, Anette; Maser-Gluth, Christiane; Remer, Thomas (Metabolism)

Glycemic index in overweight development: distinguishing limited evidence from limits in evidence - Buyken, Anette; Günther, Anke LB; Barclay, Alan; Brand-Miller, Jennie; Schulze, Matthias B (The American Journal of Clinical Nutrition)

IT Productivity and Aggregation using Income Accounting - Kundisch, Dennis; Mittal, N.; Nault, B. (10th Workshop on Information Systems and Economics (WISE))

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach considering Social Capital in the private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Proceedings of the 15th Amercas Conference on Information Systems (AMCIS))

An Evaluation Framework for Tracker Certificates during the Financial Crisis and beyond - Kundisch, Dennis; Klein, C. (International Federation of Classification Societies 2009 Conference)

Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Rezension zu L.J. Issing & P. Klimsa (Hrsg.) (2009). Online-Lernen. Handbuch für Wissenschaft und Praxis. München: Oldenbourg Verlag - Eickelmann, Birgit (Journal for Educational Research Online)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Selbstoptimierende Systeme des Maschinenbaus - Definitionen, Anwendungen, Konzepte - Adelt, P.; Donoth, J.; Gausemeier, Jürgen; Henkeler, S.; Kahl, S.; Klöpper, B.; Krupp, A.; Münch, E.; Oberthür, S.; Paiz, C.; Porrmann, M.; Radkowski, R.; et al.

Verlässlichkeit selbstoptimierender Systeme - Potenziale nutzen und Risiken vermeiden - Dell'Aere, A.; Hirsch, M.; Klöpper, B.; Koester, M.; Krüger, M.; Krupp, A.; Müller, T.; Oberthür, S.; Pook, S.; Priesterjahn, C.; Romaus, C.; Schmidt, A.; et al.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Musterbasiertes Re-Engineering von Softwaresystemen - Meyer, Matthias

Dienste-Infrastrukturen für eLearning – Konzeption, Aufbau und Betrieb - Brennecke, Andreas; Finke, Stefan; Oevel, Gudrun; Roth, A. (Hochschulentwicklung innovativ gestalten – Das Projekt Locomotion an der Universität Paderborn)

Ultranarrow coupling-induced transparency bands in hybrid plasmonic systems - Zentgraf, Thomas; Zhang, Shuang; Oulton, Rupert F.; Zhang, Xiang (Physical Review B)

Plasmon lasers at deep subwavelength scale - Oulton, Rupert F.; Sorger, Volker J.; Zentgraf, Thomas; Ma, Ren-Min; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Nature)

An optical cloak made of dielectrics - Valentine, Jason; Li, Jensen; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nature Materials)

Self-Organisation and Self-Optimization - Meyer auf der Heide, Friedhelm; Rammig, Franz-Josef (Public Service Review: Science and Technology)

Language and Logic in German Post-Hegelian Philosophy - Peckhaus, Volker (The Baltic International Yearbook of Cognition, Logic and Communication, Bd. 4: 200 Years of Analytical Philosophy)

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Algorithmische und komplexitätstheoretische Aspekte kombinatorischer Preisoptimierung (Computational Aspects of Combinatorial Pricing Problems) - Briest, Patrick (it - Information Technology)

Die Welterbeliste - zwischen Kanonbildung und Kanonverschiebung - Seng, Eva- Maria
Demnächst in: ZS ejournal Kunstgeschichte, LMU München. Open Peer Reviewed Journal www.kunstgeschichte-ejournal.net

Arno Eugen Fritsche - Seng, Eva- Maria (Protestantische Profile im Ruhrgebiet. 500 Lebensbilder aus 5 Jahrhunderten)

Denkmalpflege und kulturelles Erbe - Seng, Eva- Maria (MUT. Forum für Kultur, Politik und Geschichte)

Elias Holl - Seng, Eva- Maria (Killy-Literaturlexikon (Neuauftritt), München, Berlin)

„Aufgabe, Wirken, Möglichkeiten: 150 Jahre Kirche und Kunst in Württemberg“ - Seng, Eva- Maria (Blätter für württembergische Kirchengeschichte)

Laudatio auf Dr. Reinhard Höppner - Seng, Eva- Maria (Ehrenpromotion Höppner (Paderborner Universitätsreden 113))

Gemeinsam lernen: Der Masterstudiengang „Kulturerbe/Studies in Cultural Heritage“ - Seng, Eva- Maria (Deutsche Hochschulen im Dialog mit der arabischen Welt,)

„Phantasie oder Vernunft: Ästhetische und architektonische Visionen von Städten und Gärten“ - Seng, Eva- Maria (Ist eine andere Welt möglich? Utopische Zwischenrufe. Multidisziplinäre Analysen und Reflexionen des utopischen Denkens)

Hoffmann von Fallersleben. Internationales Symposion Corvey/Höxter 2008

Neulektüren – New Readings

Foreword - D. Kleinberg, Robert; Scheideler, Christian (Theory Comput. Syst.)

Towards a Scalable and Robust DHT - Awerbuch, Baruch; Scheideler, Christian (Theory Comput. Syst.)

Robust random number generation for peer-to-peer systems - Awerbuch, Baruch; Scheideler, Christian (Theor. Comput. Sci.)

A Distributed and Oblivious Heap - Scheideler, Christian; Schmid, Stefan (Automata, Languages and Programming, 36th Internatilonal Colloquium, ICALP 2009, Rhodes, Greece, July 5-12, 2009, Proceedings, Part II)

Epiphanische Augen-Blicke. Inszenierungen der Alltagswahrnehmung in der Prosa Wilhelm Genazinos und Angela Krauß’ - Eke, Norbert Otto (Alltag als Genre)

„Gott will mich frei“. Richard Beer-Hofmanns „Historie von König David“ - Eke, Norbert Otto (Inszenierungen der Heiligen Schrift. Jüdische und christliche Bibeltransformation vom Mittelalter bis in die Moderne)

Störsignale. René Pollesch im Prater - Eke, Norbert Otto (Ökonomie im Theater der Gegenwart. Ästhetik, Produktion, Institution)

„Ich bin der vielversprechende Jüngling, der nichts gehalten hat.“ – Werner Vordtriedes Sehnsucht nach Sprache - Eke, Norbert Otto (Jüdisches Kulturerbe in Westfalen. Spurensuche zu jüdischer Kultur in Vergangenheit und Gegenwart)

Den „Nullpunkt“ des Theaters finden. Heiner Müllers Medientheorie und Praxis - Eke, Norbert Otto (Literatur intermedial – Paradigmenbildung zwischen 1918 und 1968)

Hoffmann von Fallersleben und der Vormärz - Eke, Norbert Otto (Hoffmann von Fallersleben. Internationales Symposion Corvey/Höxter 2008)

Widersprüchliche Annäherungen – das deutschsprachige Drama - Eke, Norbert Otto (Der Nationalsozialismus – Die zweite Geschichte. Überwindung – Deutung – Erinnerung)

A Self-stabilizing and Local Delaunay Graph Construction - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Algorithms and Computation, 20th International Symposium, ISAAC 2009, Honolulu, Hawaii, USA, December 16-18, 2009. Proceedings)

Einsenkungen in Finsternisse oder: Flossenbürg liegt (nicht nur) in der Oberpfalz. Werner Fritschs Grabungen - Eke, Norbert Otto (Neulektüren – New Readings. Festschrift für Gerd Labroisse zum 80. Geburtstag)

A distributed polylogarithmic time algorithm for self-stabilizing skip graphs - Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Proceedings of the 28th Annual ACM Symposium on Principles of Distributed Computing, PODC 2009, Calgary, Alberta, Canada, August 10-12, 2009)

A DoS-resilient information system for dynamic data management - Baumgart, Matthias; Scheideler, Christian; Schmid, Stefan (SPAA 2009: Proceedings of the 21st Annual ACM Symposium on Parallelism in Algorithms and Architectures, Calgary, Alberta, Canada, August 11-13, 2009)

Brief Announcement: On the Time Complexity of Distributed Topological Self-stabilization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Stabilization, Safety, and Security of Distributed Systems, 11th International Symposium, SSS 2009, Lyon, France, November 3-6, 2009. Proceedings)

Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Algorithmic Methods for Distributed Cooperative Systems, 06.09. - 11.09.2009)

Rupeas: Ruby Powered Event Analysis DSL - Woehrle, Matthias; Plessl, Christian; Thiele, Lothar
Wireless Sensor Networks (WSNs) are unique embedded computation systems for distributed sensing of a dispersed phenomenon. While being a strongly concurrent distributed system, its embedded aspects with severe resource limitations and the wireless communication requires a fusion of technologies and methodologies from very different fields. As WSNs are deployed in remote locations for long-term unattended operation, assurance of correct functioning of the system is of prime concern. Thus, the design and development of WSNs requires specialized tools to allow for testing and debugging the system. To this end, we present a framework for analyzing and checking WSNs based on collected events during system operation. It allows for abstracting from the event trace by means of behavioral queries and uses assertions for checking the accordance of an execution to its specification. The framework is independent from WSN test platforms, applications and logging semantics and thus generally applicable for analyzing event logs of WSN test executions.
Keywords: Rupeas; DSL; WSN; testing

A Microdriver Architecture for Error Correcting Codes inside the Linux Kernel - Brinkmann, André; Eschweiler, Dominic (Journal of Supercomputing)

On Stackelberg Pricing with Computationally Bounded Consumers - Briest, Patrick; Hoefer, Martin; Gualà, Luciano; Ventre, Carmine (Lecture Notes in Computer Science)
In a Stackelberg pricing game a leader aims to set prices on a subset of a given collection of items, such as to maximize her revenue from a follower purchasing a feasible subset of the items. We focus on the case of computationally bounded followers who cannot optimize exactly over the range of all feasible subsets, but apply some publicly known algorithm to determine the set of items to purchase. This corresponds to general multi-dimensional pricing assuming that consumers cannot optimize over the full domain of their valuation functions but still aim to act rationally to the best of their ability. We consider two versions of this novel type of Stackelberg pricing games. Assuming that items are weighted objects and the follower seeks to purchase a min-cost selection of objects of some minimum weight (the Min-Knapsack problem) and uses a simple greedy 2-approximate algorithm, we show how an extension of the known single-price algorithm can be used to derive a polynomial-time (2 + ε)-approximation algorithm for the leader’s revenue maximization problem based on so-called near-uniform price assignments. We also prove the problem to be strongly NP-hard. Considering the case that items are subsets of some ground set which the follower seeks to cover (the Set-Cover problem) via a standard primal-dual approach, we prove that near-uniform price assignments fail to yield a good approximation guarantee. However, in the special case of elements with frequency 2 (the Vertex-Cover problem) it turns out that exact revenue maximization can be done in polynomial-time. This stands in sharp contrast to the fact that revenue maximization becomes APX-hard already for elements with frequency 3.

Making it relevant: Context-based learning of science [Book review] - Fechner, Sabine; Treagust, David F. (International Journal of Science Education)

Concepts for Model Verification and Validation during Simulation Runtime - Laroque, Christoph; Fischer, Matthias; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2009))
Modern companies are nowadays confronted with an increasing demand of multiple products, where they need to perform more flexible every day. Cost-intensive decisions are to be confirmed in short times, in order to minimize risks and secure efficient production programs as well as material flows. Tools for this digital planning via simulation methods are one well established possibility to receive decision support. Nevertheless, the creation of the necessary simulation models is a complicated and error-prone process, where complexity of modeling, validation and verification depends on the used tool and its functionalities. This paper presents implemented concepts for an innovative user support in his tasks of verification and validation of simulation models during the execution of a simulation run. Time-intensive procedures like stopping simulation, parameterization and restarting within the problem analysis are simplified. So the user is able to focus on the real problem solving task.

Improving Network Coded Cooperation by Soft Information - Volkhausen, Tobias; Woldegebreal, Dereje H.; Karl, Holger (2009 6th IEEE Annual Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks Workshops)

Combining for Cooperative WLANs - A Reality Check Based on Prototype Measurements - Valentin, S.; Woldegebreal, D. H.; Volkhausen, T.; Karl, Holger (2009 IEEE International Conference on Communications Workshops)

Ein System zur aggregierten Visualisierung verteilter Materialflusssimulationen - Suess, Tim; Fischer, Matthias; Huber, Daniel; Laroque, Christoph; Dangelmaier, Wilhelm (Augmented & Virtual Reality in der Produktentstehung)

Creating Butterflies in the Core – A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009)

Modeling obstacles in INET/Mobility framework: motivation, integration, and performance - Lichte, Hermann S.; Weide, Jannis (Proceedings of the Second International ICST Conference on Simulation Tools and Techniques)

Design considerations for a network of information - Ahlgren, Bengt; Vercellone, Vinicio; D'Ambrosio, Matteo; Marchisio, Marco; Marsh, Ian; Dannewitz, Christian; Ohlman, Börje; Pentikousis, Kostas; Strandberg, Ove; Rembarz, René (Proceedings of the 2008 ACM CoNEXT Conference on - CONEXT '08)

Planar Visibility Counting - Fischer, Matthias; Hilbig, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Ziegler, Martin (Proc. 25th European Workshop on Computational Geometry)
For a fixed virtual scene (=collection of simplices) S and given observer position p, how many elements of S are weakly visible (i.e. not fully occluded by others) from p? The present work explores the trade-off between query time and preprocessing space for these quantities in 2D: exactly, in the approximate deterministic, and in the probabilistic sense. We deduce the EXISTENCE of an O(m^2/n^2) space data structure for S that, given p and time O(log n), allows to approximate the ratio of occluded segments up to arbitrary constant absolute error; here m denotes the size of the Visibility Graph--which may be quadratic, but typically is just linear in the size n of the scene S. On the other hand, we present a data structure CONSTRUCTIBLE in O(n*log(n)+m^2*polylog(n)/k) preprocessing time and space with similar approximation properties and query time O(k*polylog n), where k<n is an arbitrary parameter. We describe an implementation of this approach and demonstrate the practical benefit of the parameter k to trade memory for query time in an empirical evaluation on three classes of benchmark scenes.

Measurement of effective electron mass in biaxial tensile strained silicon on insulator - Feste, Sebastian F.; Schäpers, Thomas; Buca, Dan; Zhao, Qing Tai; Knoch, Joachim; Bouhassoune, Mohammed; Schindlmayr, Arno; Mantl, Siegfried (Applied Physics Letters)
We present measurements of the effective electron mass in biaxial tensile strained silicon on insulator (SSOI) material with 1.2 GPa stress and in unstrained SOI. Hall-bar metal oxide semiconductor field effect transistors on 60 nm SSOI and SOI were fabricated and Shubnikov–de Haas oscillations in the temperature range of T=0.4–4 K for magnetic fields of B=0–10 T were measured. The effective electron mass in SSOI and SOI samples was determined as mt=(0.20±0.01)m0. This result is in excellent agreement with first-principles calculations of the effective electron mass in the presence of strain.

Überlegung zur Senkung des Energieeintrags bei der Compoundierung - Hallmann, Tobias; Schöppner, Volker; Fiekens, Nicolas; Zimmer, Detmar (VDI-Fachtagung Aufbereitungstechnik)

Methodische Modularisierung komplexer Produktstrukturen - Fiekens, Nicolas; Zimmer, Detmar (Konferenz Variantenmanagement im Produktentstehungsprozess im Maschinen- und Anlagenbau)

An Orchestration as a Service Infrastructure using Grid Technologies and WS-BPEL - Höing, Andre; Scherp, Guido; Gudenkauf, Stefan; Meister, Dirk; Brinkmann, André (Proc. Int. Conf. on Service Oriented Computing (ICSOC))

Providing Scientific Software as a Service in Consideration of Service Level Agreements - Niehörster, Oliver; Birkenheuer, Georg; Brinkmann, André; Blunk, Dirk; Elsässer, Brigitta; Herres-Pawlis, Sonja; Krüger, Jens; Niehörster, Julia; Packschies, Lars; Fels, Gregor (Proc. Cracow Grid Workshop (CGW))

Connecting Communities on the Meta-Scheduling Level: The DGSI Approach! - Birkenheuer, Georg; Carlson, Arthur; Fölling, Alexander; Högqvist, Mikael; Hoheisel, Andreas; Papaspyrou, Alexander; Rieger, Klaus; Schott, Bernhard; Ziegler, Wolfgang (Proc. Cracow Grid Workshop (CGW))

Multi-Level Comparison of Data Deduplication in a Backup Scenario - Meister, Dirk; Brinkmann, André (Proc. of the Israeli Experimental Systems Conference (SYSTOR))

Solution Patterns for the Development of Self-Optimizing Systems - Dumitrescu, Roman; Gausemeier, Jürgen; Dangelmaier, Wilhelm; Klöpper, Benjamin (Self-x in Engineering)

Control of the Pareto Optimality of Systems with Unknown Disturbances - Geisler, Jens; Trächtler, Ansgar (7th IEEE International Conference on Control & Automation (ICCA 2009))

Parametrische Modellreduktion für selbstoptimierende mechatronische Systeme - Krüger, Martin (Tagungsband Workshop GMA-Fachausschuß 1.30/1.40)

Control Strategy for the Lateral and Longitudinal Dynamics of a Fully Active X-by-wire Test Vehicle - Reinold, Peter; Nachtigal, Vitalij; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the European Control Conference 2009 (ECC))

Prototypische Applikation einer Vereinzelungsregelung an einem Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (Mechatronik 2009 VDI)

Entwicklung einer Hardware-in-the-Loop-Umgebung für den Steuergerätetest von Kondenstrocknern - Zeineldin, Tarek; Koert, Dirk; Löffler, Alexander; Trächtler, Ansgar (VDI Mechatronik)

RailCab Ein innovatives Schienenverkehrssystem für die Mobilität von morgen - Rustemeier, Carsten; Trächtler, Ansgar (Ingenieurspiegel Fachmagazin für Ingenieure)

Entwurf einer adaptiven Regelung für den Vereinzelungsvorgang in Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Aufbau und Regelung eines sturzvariablen Bahnfahrwerks mit Einzelradlenkung - Borsig, Michael; Trächtler, Ansgar; Geisler, Jens (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Echtzeitsimulation für den modellbasierten Steuergerätetest von Haushaltsgeräten - Koert, Dirk; Löffler, Alexander; Zeineldin, Tarek; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Entwurf einer semiaktiven Federung für ein leichtes Kettenfahrzeug - Illg, Igor; Jäker, Karl-Peter; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Flachheitsbasierte Reglerumschaltstrategie für Ein- und Mehrgrößensysteme - Osmic, Semir (43. Regelungstechnisches Kolloquium)

Kreuzungsmanagement: Trajektorienplanung mittels dynamischer Programmierung - Bruns, Torsten; Trächtler, Ansgar (at-Automatisierungstechnik)

Verlässlichkeit im aktiven selbstoptimierenden Spurführungsmodul eines schienengebundenen Fahrzeugs - Sondermann-Wölke, Christoph; Geisler, Jens; Hirsch, Martin; Hemsel, Tobias (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Selbstoptimierende Systeme des Maschinenbaus Definitionen, Anwendungen, Konzepte - Adelt, Philipp; Donoth, Jörg; Gausemeier, Jürgen; Geisler, Jens; Henkler, Stefan; Kahl, Sascha; Klöpper, Benjamin; Krupp, Alexander; Münch, Eckehard; Oberthür, Simon; Paiz, Carlos; Porrmann, Mario; et al. (HNI-Verlagsschriftenreihe)